Empowering the DPRS for effective performance in the 21st century : proceedings of the Sixth Annual DPRS Directors Conference, held in Ibadan, from 21-25 June 1999 - Obadan, Michael I.; Uga, Edu O.; National Centre for Economic Management and Administration (Nigeria) (Ibadan, Nigeria : National Centre for Economic Management and Administration, 2000)
The book is a collection thoughts on economic policy reforms during the mid 1980s serious economic and financial problems that became manifest from the beginning of that decade. The DPRS was part of the reform of that era.
Includes bibliographical references.
sju 25/01/2019, ijb 06/02/2019
Loans
Keywords: Administrative agencies; Civil service reform; Nigeria